Political repressions against Kyrgyz and Kazakh elite in the 1930s and their implications - B., Sarsenbayev (Opción, 2020)
Mass political repression of the Stalin era, especially the campaigns of the 1930s to eradicate a variety of “party inclinations lines” and “bourgeois nationalism,” inflicted a severe blow to the Kyrgyz and Kazakh elite. Several negative consequences of repression are still felt and affect the Direction & features of development in Kyrgyzstan and Kazakhstan. With scientific and political significance, this issue is not studied adequately and remains debatable in the historical science in both Republics. It is advisable to study Repression against Kyrgyz and Kazakh elite together since they were almost identical and led to similar consequences, for several reasons.